2021
DOI: 10.1039/d0dt04286b
|View full text |Cite
|
Sign up to set email alerts
|

The structural manipulation of a series of Ni4 defective dicubanes: Synthesis, X-ray Structures, Magnetic and Computational analyses

Abstract: We report the synthesis and characterization of four new tetranuclear Ni(II) complexes, C1-C4, all of which exhibit defective dicubane cores. The complexes C1-C4 are derived from the same salicylaldoxime derived...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…17,18 As such, the effect of having both elongation and compression distortions on the magnetic exchange between two Mn III centres has not yet been determined. Among our group's work on derivatised salicylaldoximes, [28][29][30][31][32][33][34] the crystal structure of a complex featuring two manganese coordination centres in distorted octahedral environments: one elongated and the other compressed was obtained (Fig. 1, ESI †).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 As such, the effect of having both elongation and compression distortions on the magnetic exchange between two Mn III centres has not yet been determined. Among our group's work on derivatised salicylaldoximes, [28][29][30][31][32][33][34] the crystal structure of a complex featuring two manganese coordination centres in distorted octahedral environments: one elongated and the other compressed was obtained (Fig. 1, ESI †).…”
Section: Introductionmentioning
confidence: 99%
“…83 They found that (35) displayed some SMM behaviours whilst ( 36) and (37) did not, which is not unreasonable since La III is diamagnetic and Gd III is typically magnetically isotropic. The observed out-of-phase ac magnetic susceptibility (χ″) measurements on (35) showed frequency dependence between 1.9 K and 4.2 K however, there was no clear (χ″) maxima within the experimental temperature and frequency ranges. This absence was a result of fast QTM bypassing the energy barrier.…”
Section: Changing Electron Densitymentioning
confidence: 83%
“…33,34 These computational methods tend to agree well with the experimental results whilst providing researchers a way to probe how small structural differences between SMMs can affect their magnetic properties. 35…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our goal for this research was to investigate the relative stability of a series of transition metal complexes, specifically dinuclear homo- and heterometallic, and their associated magnetic properties. Our complex framework stems from the ligand, H 2 L (6,6′-dimethoxy-2,2’-[(1,3-propylene)dioxybis(nitrilomethylidyne)]diphenol), which was chosen as it has two distinct coordination environments (Figure ), and the literature has shown that its analogues are capable of producing polynuclear, specifically dinuclear, complexes. ,, Our group has previously reported several exciting polynuclear structures with interesting magnetic and/or structural properties. In this research, we report the synthesis, transmetalation, X-ray structures, and computational and magnetic analyses of three dimeric complexes, CuCu ( [ C u 2 I I L ( N O 3 ) 2 ] ), MnMn ( [ M n 2 I I L ( M e O H ) 2 ( N O 3 ) 2 ] ), and CuMn ([Cu II Mn II L (NO 3 ) 2 ]). The labeling of the complexes is directly related to the metal ions occupying the coordination pockets (M1M2, Figure ).…”
Section: Introductionmentioning
confidence: 99%